2001
DOI: 10.1038/35055518
|View full text |Cite
|
Sign up to set email alerts
|

Strong radiative heating due to the mixing state of black carbon in atmospheric aerosols

Abstract: Aerosols affect the Earth's temperature and climate by altering the radiative properties of the atmosphere. A large positive component of this radiative forcing from aerosols is due to black carbon--soot--that is released from the burning of fossil fuel and biomass, and, to a lesser extent, natural fires, but the exact forcing is affected by how black carbon is mixed with other aerosol constituents. From studies of aerosol radiative forcing, it is known that black carbon can exist in one of several possible mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,654
2
20

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,308 publications
(1,744 citation statements)
references
References 20 publications
27
1,654
2
20
Order By: Relevance
“…For example, Yang et al (2011) observed that most submicron carbonaceous aerosols were internally mixed with ammonium nitrate and secondary organic compounds during the HH episode of Shanghai winter. Both theory and practice have demonstrated that the absorption efficiency (σ ap ) of EC in the internal mixing pattern is much higher than that in the external mixing pattern (Jacobson 2001;Ramanathan and Carmichael 2008;Bond et al 2013). Apparently, this trend will partially (rather than completely) account for the higher BC levels observed under HH conditions in comparison to EC unambiguously.…”
Section: Exploratory Probe Of the Bc/ec Divergence In The Hh Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Yang et al (2011) observed that most submicron carbonaceous aerosols were internally mixed with ammonium nitrate and secondary organic compounds during the HH episode of Shanghai winter. Both theory and practice have demonstrated that the absorption efficiency (σ ap ) of EC in the internal mixing pattern is much higher than that in the external mixing pattern (Jacobson 2001;Ramanathan and Carmichael 2008;Bond et al 2013). Apparently, this trend will partially (rather than completely) account for the higher BC levels observed under HH conditions in comparison to EC unambiguously.…”
Section: Exploratory Probe Of the Bc/ec Divergence In The Hh Periodmentioning
confidence: 99%
“…The past three decades have seen increasing interest in black carbon (BC) and elemental carbon (EC), both of which originate from the incomplete combustion of carbonaceous combustibles, due to their strong light-absorbing properties and their possible health effects (Johnson and Huntzicker 1979;Wolff 1981;Turco et al 1983;Molnar et al 1999;Jacobson 2000Jacobson , 2001Ramanathan and Carmichael 2008;Allen et al 2012). EC represents thermally refractory carbon with a graphitic structure, whereas BC is commonly used to define the extent to which an aerosol sample exhibits light-absorbing properties (Salako et al 2012;Gray and Cass 1998;Huntzicker et al 1982;Watson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, biomass burning particles can have a completely opposite behavior, depending on their content in organic and black carbon, on their size and on their spatial distribution in the atmosphere. These properties of the biomass burning aerosol particles are affected by source type, combustion type and phase (Martins et al, 1998;Jacobson, 2001;Reid et al, 2005a, b) and so-called aging processes caused by different mechanisms such as photochemical oxidation (Grieshop et al, 2009a, b), hygroscopic growth (Hobbs et Published by Copernicus Publications on behalf of the European Geosciences Union. Granados-Muñoz et al, 2015;Titos et al, 2014aTitos et al, , b, 2016 or coagulation (Fiebig et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2 The contribution of soot to global warming may be second only to that of CO 2 . 3 Soot also poses a health risk by causing and enhancing respiratory, cardiovascular, and allergic diseases. 4 In addition, soot particles are expected to be active in heterogeneous reactions with gaseous pollutants like NO 2 , H 2 SO 4 , and O 3 5−9 significantly affecting the chemical composition of the atmosphere and thus influencing their climatic and health effects.…”
Section: Introductionmentioning
confidence: 99%